Ligand‐Controlled Doping Effects in Alloy Nanoclusters Au4Ag23 and Au5Ag24. Issue 60 (17th October 2018) - Du, Yang; Guan, Zong‐Jie; Wen, Zhao‐Rui; Lin, Yu‐Mei; Wang, Quan‐Ming
Abstract: The syntheses and properties of two bimetallic nanoclusters [Au4 Ag23 (C≡C t Bu)10 (dppf)4 Cl7 ](PF6 )2 and [Au5 Ag24 (C≡CC6 H4 ‐ p ‐ t Bu)16 (dppf)4 Cl4 ](PF6 )3 are reported. The Au atoms distributed in both the cores and the surface motifs are clearly determined. The two nanoclusters show distinctly different geometric structures and electronic properties, which are attributed to the subtle changes in the surface alkynyl structures. Abstract : Cluster control : Two different alloy Au4 Ag23 and Au5 Ag24 nanoclusters are induced by a subtle change of the groups on their alkynyl ligands (see figure).